Macrosyntactic and discursive analysis of 'te lo prometo' - Prestigiacomo, Carla (Círculo de Lingüística Aplicada a la Comunicación, 2019)
The purpose of this paper is to describe the discursive behaviour of te lo prometo, from a pragma-linguistic and argumentative perspective. After a brief description of its macrosyntactic behavior (its position inside the statement, function of the pauses, combination with other linguistic elements ...), I demonstrate how te lo prometo is undergoing a grammaticalization process: it is losing its original meaning, to acquire strategic discursive functions (intensifier of the assertion, element of argumentative force, element of (im)politeness, irony ...) in informal argumentative texts.
Keywords: macrosyntaxis; argumentation; persuasion; discourse markers